2020
DOI: 10.1186/s12879-020-05578-3
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Xpert® MTB/RIF in diagnosing tuberculous pleuritis using thoracoscopic pleural biopsy

Abstract: Background Etiological diagnosis of tuberculous pleuritis is challenging, owing to a paucity of Mycobacterium tuberculosis (MTB) in the affected region. Moreover, currently available methods, such as the detection of acid-fast bacilli and microbiological culture, are not always conducive to timely diagnosis and treatment. In this study, we evaluated the performance of Xpert® MTB/RIF assay (hereinafter referred to as “Xpert”) in detecting MTB in difficult-to-diagnose patients using suspensions of pleural biopsy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 18 publications
5
9
0
Order By: Relevance
“…High specificity with a small sample size is not reliable. One study showed 65% specificity when compared with a composite reference standard (CRS), 16 almost comparable with our results. The positive predictive value was 22.2%, the negative predictive value was 52.1% and the area under the curve (ROC) was 58% in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…High specificity with a small sample size is not reliable. One study showed 65% specificity when compared with a composite reference standard (CRS), 16 almost comparable with our results. The positive predictive value was 22.2%, the negative predictive value was 52.1% and the area under the curve (ROC) was 58% in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Results from previous studies are conflicting in this regard. The positive predictive value and negative predictive value of GeneXpert were 56.4 and 75.6%, respectively in a study conducted in China, 16 supporting our results. The positive predictive value was 100% in a local study conducted in Karachi, 14 but pleural tissue was used instead of pleural fluid, which may be the cause of the high positive predictive value in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The sensitivity of TB-LAMP was 67.2% lower than that of pathology at 77.7% ( P < 0.05). In our previous study, which also evaluated the positivity rate of pleural biopsy at endoscopy in 113 patients with pleural tuberculosis, 71 patients (71/113 62.8%) were positive for caseous granuloma, a result similar to the findings of the present study ( 19 ). TB-LAMP has an additional advantage over pathology in areas with a high burden of TB.…”
Section: Discussionsupporting
confidence: 90%
“…Data regarding the performance of this assay in pleural tissue samples and against the composite reference standard is scarce: the aforementioned Cochrane analysis only found a single study on this topic including 55 patients, 14 out of them with tuberculous effusions, and with surprising and disappointing results (sensitivity of 0%, specificity of 98%) [66]. Subsequently, three additional studies of 73, 113 and 27 patients diagnosed with TPE and who underwent thoracoscopic pleural biopsy reported a sensitivity of the Xpert MTB/RIF assay of 45%, 69% and 85%, respectively in pleural tissue samples against the composite reference standard [68][69][70]. Our study showed a five-fold higher sensitivity of the Xpert MTB/RIF assay in pleural tissue compared to pleural fluid (57% versus 11%), and close to that obtained with culture of pleural fluid (56%) or closed biopsy pleural specimens (58%).…”
Section: Plos Onementioning
confidence: 99%